1re

Suites : généralités

Ce quiz comporte 6 questions


facile

1re - Suites : généralités1

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

{u0=3un+1=un1\begin{cases} u_0=3 \\u_{n+1}=u_n-1 \end{cases}

Alors : u3=0u_3=0

1re - Suites : généralités1
1re - Suites : généralités1
1re - Suites : généralités1

C'est vrai :

u1=u01=2 u_1 = u_0 -1=2

u2=u11=1 u_2 = u_1 -1=1

u3=u21=0 u_3 =u_2 -1=0

1re - Suites : généralités2

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

un=1n+1u_n= \frac{ 1 }{ \sqrt{ n+1 } }

Alors : u3=0,5u_{3}=0,5

1re - Suites : généralités2
1re - Suites : généralités2
1re - Suites : généralités2

C'est vrai :

u3==13+1=14=12=0,5u_{3}== \frac{ 1 }{ \sqrt{ 3+1 } }= \frac{ 1 }{ \sqrt{ 4 }} = \frac{ 1 }{ 2} =0,5

1re - Suites : généralités3

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

{u0=1un+1=2un\begin{cases} u_0=1 \\u_{n+1}=2-\sqrt{u_n} \end{cases}

Alors : u10=1u_{10}=1

1re - Suites : généralités3
1re - Suites : généralités3
1re - Suites : généralités3

C'est vrai :

u1=2u0=21=1 u_1 = 2-\sqrt{u_0} = 2-1=1

u2=2u1=21=1 u_2 = 2-\sqrt{u_1} = 2-1=1

etc.

u10=2u9=21=1 u_{10} = 2-\sqrt{u_9} = 2-1=1

1re - Suites : généralités4

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

{u0=1un+1=nun\begin{cases} u_0=1 \\u_{n+1}=nu_n \end{cases}

Alors : u3=6u_3=6

1re - Suites : généralités4
1re - Suites : généralités4
1re - Suites : généralités4

C'est faux :

u1=0×u0=0 u_1 = 0 \times u_0=0

u2=1×u1=0 u_2 = 1 \times u_1=0

u3=2×u2=0 u_3 = 2 \times u_2=0

1re - Suites : généralités5

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

{u0=4un+1=un2+1\begin{cases} u_0=4 \\u_{n+1}=\dfrac{u_n}{2}+1 \end{cases}

Alors : u2=52u_2=\dfrac{5}{2}

1re - Suites : généralités5
1re - Suites : généralités5
1re - Suites : généralités5

C'est vrai :

u1=u02+1=42+1=3 u_1 = \dfrac{u_0}{2}+1=\dfrac{4}{2}+1 = 3

u2=u12+1=32+1=52 u_2 = \dfrac{u_1}{2}+1=\dfrac{3}{2}+1 = \dfrac{5}{2}

1re - Suites : généralités6

Soit la suite (un)(u_n) définie sur N\mathbb{N} par :

{u0=1un+1=un+n\begin{cases} u_0=1 \\u_{n+1}=u_n+n \end{cases}

Alors :

u3=5u_3=5

1re - Suites : généralités6
1re - Suites : généralités6
1re - Suites : généralités6

C'est faux :

u1=u0+0=1 u_1 = u_0+0=1

u2=u1+1=2 u_2 = u_1+1 =2

u3=u2+2=4 u_{3} = u_2+2=4